La fabrique séculière du droit musulman : Vers une anthropologie politique de la religion - Landry, Jean-Michel (Anthropologica, 2022)
Fatima Hamza, a Lebanese citizen, was incarcerated in November 2016 for refusing to grant her ex-husband custody of their young son. Since the custody case was adjudicated by a religious judge, many understood her punishment as yet another proof that Islamic law is unjust. In tracking the history of recent campaigns aiming at reforming custody law, a different kind of analysis emerges. Such an analysis shows that the Lebanese state contributes to shape the religious laws enforced by Sharia judges. It also highlights that we cannot appreciate the practice of Islamic family law today without also considering the ways in which secular states regulates what they describe as religious.